2008
DOI: 10.1016/j.jtcvs.2007.10.042
|View full text |Cite
|
Sign up to set email alerts
|

Optimal timing of coronary artery bypass after acute myocardial infarction: A review of California discharge data

Abstract: Patients undergoing coronary artery bypass grafting within 2 days of hospitalization for acute myocardial infarction experienced higher mortality rates than those undergoing coronary artery bypass grafting 3 or more days after acute myocardial infarction, independently of clinical acuity. This suggests that coronary artery bypass grafting may best be deferred for 3 or more days after admission for acute myocardial infarction in nonurgent cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
86
1
7

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(97 citation statements)
references
References 24 publications
3
86
1
7
Order By: Relevance
“…In our study, neither group A nor B predicted HM, which was marginally lower (6.0%) in our series than theirs (6.3%). A review of the California Discharge data by Weiss and coworkers 17 also reported a significantly higher mortality rate of 5.6% among patients undergoing early CABG (0-2 days) compared with 3.6% for late CABG (>3 days) with a peak mortality of 8.2% on day 0 after acute MI. Of note, the above-mentioned studies included both STEMI and NSTEMI patients, and the latter analysis had a lower percentage of subendocardial infarcts (45% versus 61%; P<0.001) in the early CABG group.…”
Section: Discussionmentioning
confidence: 97%
“…In our study, neither group A nor B predicted HM, which was marginally lower (6.0%) in our series than theirs (6.3%). A review of the California Discharge data by Weiss and coworkers 17 also reported a significantly higher mortality rate of 5.6% among patients undergoing early CABG (0-2 days) compared with 3.6% for late CABG (>3 days) with a peak mortality of 8.2% on day 0 after acute MI. Of note, the above-mentioned studies included both STEMI and NSTEMI patients, and the latter analysis had a lower percentage of subendocardial infarcts (45% versus 61%; P<0.001) in the early CABG group.…”
Section: Discussionmentioning
confidence: 97%
“…W przeglądzie kalifornijskich danych wypisowych porównano pacjentów z MI poddanych wczesnemu CABG (< 3 dni, n = 4676) z poddanymi odroczonemu CABG (≥ 3 dni, n = 4800) [362]. Pacjentów wcześnie leczonych za pomocą CABG charakteryzowała większa śmiertelność niż chorych poddanych odroczonemu CABG [nieskorygowana śmiertelność: 5,6% vs. 3,8%; skorygowany metodą propensity OR 1,40 (95% CI 1,12-1,74); p < 0,001], z najwyższą śmiertelnością w grupie pacjentów operowanych w dniu rozpoznania MI (8,2%).…”
Section: Przetoczenie Preparatów Krwiunclassified
“…The weekly schedule of the operation has been studied as a determinant of outcomes, since elective surgery is usually scheduled for weekdays during 'normal' working hours (43)(44)(45)(46). Regarding the preoperative risk factors for postoperative pulmonary functions, this factor was not a main determinant of postoperative risk status.…”
Section: Operating Room Management Factorsmentioning
confidence: 99%
“…Female patients seem to be at a slightly higher risk of postoperative respiratory complications (1)(2)(3)(44)(45)(46)(47)(48).…”
Section: Gendermentioning
confidence: 99%